2018
DOI: 10.5505/tjtes.2018.91679
|View full text |Cite
|
Sign up to set email alerts
|

The ANK Nail Treatment of the Lateral Malleolar Fractures With Syndesmosis Injury; Clinical Outcomes at 10 Years Follow up.

Abstract: BACKGROUND: Lateral malleolar fractures associated with syndesmotic injuries are common. Various surgical implants may be used for the management of syndesmosis injury. One of these is ANK nail. The aim of the present study was to assess the clinical and radiological outcomes of patients treated with ANK nail. METHODS:Forty-eight patients who were followed up for a minimum of 10 years were reviewed retrospectively using American Orthopedic Foot and Ankle Society (AOFAS) score, radiological evaluation, and deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…2 Our study did not take into consideration a particular technique to take care of syndysmotic tear in Weber type B ankle fracture, many similar studies reported use of different intramedulary devices for lateral fibular fracture in their studies; they made use of ANK (Ayhan Nedim Kara) nail for communited and oblique fractures that had associated syndesmotic ligament tear with great postoperative success. 22,23 Although our study made use of nonlocked 3mm K-wire, the biomechanical strength cannot be compared with both conventional locked nail and plate fixation as reported by other biomechanical studies performed to compare use of IM nail and plates for treatment of both comminuted and non-comminuted fractures of the distal third of fibula. 8,9 However, use of K-wire as an implant for the fixation is quite relevant and justifiable as the fibula is not a full-weight bearing bone, though its distal part is integral to the stability of the ankle joint.…”
Section: And 6)mentioning
confidence: 97%
“…2 Our study did not take into consideration a particular technique to take care of syndysmotic tear in Weber type B ankle fracture, many similar studies reported use of different intramedulary devices for lateral fibular fracture in their studies; they made use of ANK (Ayhan Nedim Kara) nail for communited and oblique fractures that had associated syndesmotic ligament tear with great postoperative success. 22,23 Although our study made use of nonlocked 3mm K-wire, the biomechanical strength cannot be compared with both conventional locked nail and plate fixation as reported by other biomechanical studies performed to compare use of IM nail and plates for treatment of both comminuted and non-comminuted fractures of the distal third of fibula. 8,9 However, use of K-wire as an implant for the fixation is quite relevant and justifiable as the fibula is not a full-weight bearing bone, though its distal part is integral to the stability of the ankle joint.…”
Section: And 6)mentioning
confidence: 97%
“…Weber C fractures are more likely to be associated with injury to the syndesmosis. 10,21 Children with open physes can have Salter-Harris fractures in the fibula and tibia; thus, ankle fracture classification systems such as Dias-Tachdjian have been developed for pediatric populations. [22][23][24] An open physis more often leads to certain fractures found in children and is thought to be a protective factor against syndesmotic injury.…”
Section: Mechanism Of Injurymentioning
confidence: 99%